Multiplier Left Hopf Algebras - Chunxiao Yan; Shuanhong Wang (Mathematics)
In this paper, we introduce and study the notion of a multiplier left Hopf algebra, which can be seen as an extension of the Van Daele’s multiplier Hopf algebras and the Green–Nichols–Taft’s left Hopf algebras. In particular, we investigate the relation between the notion of the Van Daele’s left multiplier Hopf algebras and the one of our multiplier left Hopf algebras. Finally, we determine the case when a multiplier left Hopf algebra becomes a multiplier Hopf algebra.